Resistance and Adaptability in Change Management at Vocational High School in West Java, Indonesia - Sutarni, Nani; Winata, Hendri; Hufad, Achmad; Wulandari, Puspita; Kusnendi, K. (Journal of Technical Education and Training, 2022)
The purpose of this study is to analyze the influence of resistance to change and adaptability to change on change management at Vocational High School (VHS) in West Java, Indonesia. Using the survey and quantitative approach, the research was conducted at 61 VHS in 27 regencies/cities in West Java, with a representative sample of 183 teachers. The data were analyzed by descriptive and Partial Least Square (PLS). It is found that resistance to change has a negative influence on change management, and that adaptability to change has a positive influence on change management.  Thus, the schools have a low tendency to resist because they have the certainty to participate in the changes and have the willingness to undertake the programs to support the emergent changes. The schools have a high propensity to handle change management because they have high dynamic adaptability to change. This study is expected to have an impact on the school management to get a better picture of how to manage the changes effectively and efficiently, and on the government, industry, and community to interactively design the support system in the process of change management at vocational schools.